Insecticidal and knockdown resistance status of Anopheles gambiae s.l (Diptera: Culicidae) to pyrethroid and organophosphate insecticides in Osun State, Nigeria - Lateef Oluwatoyin Busari; Zarat Oyindamola Iwalewa; Olabanji Ahmed Surakat; Adedapo Olufemi Adeogun; Akinlabi Mohammad Rufai; Kamilu Ayo Fasasi; Monsuru Adebayo Adeleke (PLoS ONE, 2026)
Insecticide resistance in malaria vectors remains a global public health problem; however, little is known about resistance levels in Osun State, despite relatively high rates of malaria and distribution of insecticide-treated nets in the area. This study evaluates the resistance status of adult female Anopheles gambiae s.l to pyrethroids (permethrin, deltamethrin and alpha-cypermethrin) and an organophosphate (pirimiphos-methyl) insecticides and knockdown resistant (KDR) gene detection in six locations (Ido-Osun, Ipetumodu, Inisa, Ejigbo, Ijebu-Jesha and Ila) across the three senatorial districts in Osun State, Nigeria. Larval sampling was done between 0700hr and 1100hrs weekly between January and December 2022. Collected larvae were reared to the adult stage in the Department of Animal and Environmental Biology laboratory of Osun State University, Osogbo, Nigeria and then identified morphologically using morphological keys. Insecticide bioassay was conducted with permethrin (0.75%), deltamethrin (0.05%), alpha-cypermethrin (0.05%) and pirimiphos-methyl (0.25%) using WHO procedure. The mosquitoes were subjected to molecular analysis to detect the KDR gene. Pirimiphos-methyl showed significantly higher knockdown at 60 minutes (KD60) and achieved 100% mortality compared with the pyrethroids tested (p < 0.05), with no resistance detected across the study areas. Overall, pyrethroid mortality ranged from 40% to 97% across the study sites, indicating suspected to confirmed resistance. The lowest mortality was recorded at Ila for permethrin (86%) and at Ejigbo for alpha-cypermethrin (60%) and deltamethrin (40%)”. In addition, there was the detection of the KDR gene across the study areas. The present study reveals the insecticidal efficacy of pirimiphos-methyl against female Anopheles gambiae s.l as compared to pyrethroids. Therefore, there is a need to intensify insecticide resistance surveillance of Anopheles in Osun State to plan indoor residual spraying with pirimiphos-methyl and explore the use of PBO or dual active ingredient insecticides treated nets (ITNs) to address the potential impacts of pyrethroid resistance.